β-defensin-4 as an endogenous biomarker in cows with mastitis - Neumann, Stephan; Siegert, Stephan; Fischer, Anneke (Frontiers in Veterinary Science, 2023)
Defensins are antimicrobial peptides. Their altering concentration during infections provides information on prognosis and course of diseases. The aim was to find possible correlations between -Defensin-4 (DEFB-4) concentrations in milk and serum of cows with mastitis on the one hand and clinical symptoms and disease progression on the other hand. 85 dairy cows were examined. 30 animals suffered from acute clinical mastitis, 25 animals were diagnosed with subclinical mastitis; 30 animals served as healthy control group. Animals with mastitis were re-examined after 12 days. Additionally, four cows with acute clinical mastitis were examined and sampled every two weeks until seven weeks after antibiotic treatment to follow DEFB-4 levels over a longer time period. DEFB-4 levels were determined by a species-specific ELISA. The highest concentrations of DEFB-4 were found in cows with acute clinical mastitis (median of 115 pg/mL (milk); median of 245 pg/mL (serum)). In serum the concentrations of this group differed significantly from the healthy control group (p = 0.02), a lower median of 153 pg/mL was detected. In milk the median of the healthy control group was also lower (97 pg/mL), but not significant. We found that concentrations of DEFB-4 in milk and serum of cows with acute mastitis were significantly higher than those of cows with subclinical mastitis (p < 0.0001 serum; p = 0.015 milk). In this group median concentrations of 46 pg/mL were detected in milk and 85 pg/mL in serum. In relation to the progression of the disease it was found that DEFB-4 levels remained high for the whole observation period, suggesting that the animals had not fully recovered even seven weeks after the onset of acute clinical mastitis. In conclusion, our results revealed the possibility to differentiate between cows with acute mastitis and healthy cows by determining DEFB-4 concentrations in serum. Since DEFB-4 concentrations in animals with clinical mastitis, that required antibiotic treatment, differed significantly from those in animals with subclinical mastitis, that did not require antibiotic treatment, we propose that DEFB-4 may be used as an endogenous biomarker which could help to support the rational use of antibiotics in the future.